Sport-specific assessment of lactate threshold and aerobic capacity throughout a collegiate hockey season - Durocher, J. J.; Leetun, D. T.; Carter, J. R. (Applied Physiology, Nutrition, and Metabolism, 2008)
The purpose of this study was to examine lactate threshold (LT) and maximal aerobic capacity with a sport-specific skating protocol throughout a competitive season in collegiate hockey players. We hypothesized that maximal aerobic capacity and skating velocity at LT would increase as the season progressed. Sixteen Division I college hockey players performed a graded exercise skating protocol to fatigue at 3 different times (pre-, mid-, and postseason). Subjects skated for 80 s during each stage, followed by 40 s of rest to allow for blood lactate sampling. Velocity at LT was similar during preseason (4.44 ± 0.08 m·s-1) and postseason (4.52 ± 0.05 m/s) testing, but was significantly elevated at midseason (4.70 ± 0.08 m·s-1; p < 0.01), compared with preseason. In contrast, LT as a percentage of maximal heart rate (HRmax) was unchanged throughout the season. HRmax remained constant throughout the season, at approximately 190 beats/min. Preseason maximal aerobic capacity (48.7 ± 0.8 mL/kg·min) was significantly higher than that at postseason (45.0 ± 1.1 mL/kg·min; p < 0.01). In conclusion, skating velocity at LT improved from pre- to midseason, but this adaptation was not maintained at postseason. Additionally, maximal aerobic capacity was reduced from pre- to postseason. These findings suggest a need for aerobic training throughout the college hockey season.